Sobrepeso pré-gestacional associa-se a ganho ponderal excessivo na gestação - Carvalhaes, Maria Antonieta De Barros Leite [UNESP] (2013)
PURPOSE: To evaluate the adequacy of gestational weight gain and to determine its association with maternal socioeconomic, demographic and nutritional factors and health care, to estimate the prevalence of low birth weight, macrosomia, preterm birth and cesarean delivery and to identify the association of these outcomes with the adequacy of weight gain. METHODS: A cross-sectional study was performed in 2009/2010 to obtain socioeconomic, demographic, nutritional, dietary and physical activity data of pregnant women assisted by primary health care in a municipality of the state of São Paulo. Subsequently, data were collected from the medical records to evaluate gestational weight gain. Type of delivery, birth weight and gestational age at delivery were obtained from the Livebirths Information System. Gestational weight gain was evaluated according to the recommendations of the Institute of Medicine (2009). Associations were investigated by comparing the frequencies and by logistic regression, with excessive weight gain (yes, no) and insufficient gain (yes, no) being the dependent variables. RESULTS: A total of 212 pregnant women were studied: 50.5% had excessive gain and 19.8% insufficient weight gain. Only prepregnancy nutritional status was associated with adequacy of weight gain: compared with normal weight, prepregnancy overweight women had a four-fold higher chance to gain excessive weight (OR 4.66, 95%CI 2.19-9.4). Nearly a third of babies were born by caesarian section, 5.7% were premature, 7.1% were underweight and 4.7% were macrosomic. There was no association between adequacy of gestational weight gain and these outcomes. CONCLUSION: The proportion of inadequate gestational weight gain was high. Overweight pregnant women have a four-fold higher chance to gain excessive weight, and priority should be given to actions promoting adequate prenatal weight gain.